Incidence of bloodstream infections: a nationwide surveillance of acute care hospitals in Switzerland 2008–2014. Issue 3 (21st March 2017) - Buetti, Niccolò; Atkinson, Andrew; Marschall, Jonas; Kronenberg, Andreas; ,
Abstract : Background: Bloodstream infections are often associated with significant mortality and morbidity. We aimed to investigate changes in the epidemiology of bloodstream infections in Switzerland between 2008 and 2014. Methods: Data on bloodstream infections were obtained from the Swiss antibiotic resistance surveillance system (ANRESIS). Results: The incidence of bloodstream infections increased throughout the study period, especially among elderly patients and those receiving care in emergency departments and university hospitals. Escherichia coli was the predominant pathogen, with Enterococci exhibiting the most prominent increase over the study period. Conclusions: The described trends may impact morbidity, mortality and healthcare costs associated with bloodstream infections.